Pemberdayaan UMKM melalui Digitalisasi Akuntansi dan Analisis Laporan Keuangan Berbasis Cloud pada Jamjoom Parfume - Cici Rosmala; Aulia Rahmi; Ari Sarah Sofura; Satria Berbudi (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to the Indonesian economy, particularly in job creation and increasing community income. In the context of rapid information technology development, MSMEs must adapt to digital transformation to improve operational efficiency and business competitiveness. Jamjoom Parfume, an MSME engaged in the sale and distribution of perfume products, faces an increasing need for an integrated financial management system due to growing business activities and transaction volume. To address this need, the community service team implemented an MSME empowerment program through accounting digitalization and cloud-based financial report analysis. The program included training on cloud-based accounting applications for recording financial transactions, assistance in preparing financial reports such as profit and loss statements, statements of financial position, and cash flow statements, as well as training in monitoring and evaluating the implementation of cloud-based accounting systems. These activities aimed to ensure program sustainability and measure business performance based on profitability, liquidity, and efficiency indicators. The results show that partners gained a better understanding of business financial conditions, including revenue, operational costs, profit, assets, and liabilities through systematic financial reports.